Engaging "seldom heard" groups in research and intervention development: Offender mental health. (20th July 2018) - Taylor, Charlie; Gill, Laura; Gibson, Andy; Byng, Richard; Quinn, Cath
Abstract: Background: People subject to the criminal justice system often have substantially different life‐experiences from the general population. Patient and public involvement (PPI) of "seldom heard" groups provides valuable experiential knowledge, enhancing research. Objective: To share our jointly developed techniques to ensure the meaningful engagement and contribution of people with lived experience of the criminal justice system (PWLECJS) in research, trial science, intervention theory development and dissemination. Methods: Commitment to adequate financial resources, appropriate staff skills and adequate time were combined with previous learning. PWLECJS were approached through local community organizations. A group was established and met fortnightly for ten months in an unthreatening environment and had a rolling membership. Ongoing engagement was promoted by the group taking responsibility for the rules, interactive and accessible activities, feeding back tangible impacts, ongoing contact, building a work ethic, joint celebrations, sessions with individual academic researchers and pro‐actively managed endings. Results: The Peer Researchers contributed to study documents, training academic researchers, research data collection and analysis, intervention delivery and theory development and trial science. The Peer Researchers gained in confidence and an improved sense of self‐worth. The Academic Researchers gained skills, knowledge and an increased openness to being challenged. Discussion and conclusions: PWLECJS can be meaningful included in health research and intervention development. The key elements required are listed. Challenges included differences in priorities for timescales and dissemination, resource limitations and the use of Peer Researchers' names. Further research is required to understand what might be of relevance for other "seldom heard" groups.